2021
DOI: 10.1029/2020gl091699
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Influence of COVID‐19 on the Shortwave Radiative Fluxes Over the East Asian Marginal Seas

Abstract: The Coronavirus Disease 2019 (COVID‐19) pandemic led to a widespread reduction in aerosol emissions. Using satellite observations and climate model simulations, we study the underlying mechanisms of the large decreases in solar clear‐sky reflection (3.8 W m−2 or 7%) and aerosol optical depth (0.16 W m−2 or 32%) observed over the East Asian Marginal Seas in March 2020. By separating the impacts from meteorology and emissions in the model simulations, we find that about one‐third of the clear‐sky anomalies can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 34 publications
(45 reference statements)
3
24
0
Order By: Relevance
“…While both events perturb the TOA radiative imbalance, with detectable impacts on hemispheric energy budgets and surface temperature, the intensity and timescales of both the forcings and responses are found to differ considerably. The effects of COVID are generally subtle and gradual, and on a large scale are a challenge to distinguish from internal variability, as also discussed in Ming et al (2021) and Loeb et al (2021). In contrast, as shown in this and other recent works (Hirsch & Koren, 2021;Khaykin et al, 2020), the AF emissions anomalies are relatively brief but intense, and associated climate responses in FASULLO ET AL.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…While both events perturb the TOA radiative imbalance, with detectable impacts on hemispheric energy budgets and surface temperature, the intensity and timescales of both the forcings and responses are found to differ considerably. The effects of COVID are generally subtle and gradual, and on a large scale are a challenge to distinguish from internal variability, as also discussed in Ming et al (2021) and Loeb et al (2021). In contrast, as shown in this and other recent works (Hirsch & Koren, 2021;Khaykin et al, 2020), the AF emissions anomalies are relatively brief but intense, and associated climate responses in FASULLO ET AL.…”
Section: Discussionmentioning
confidence: 62%
“…Detectable anomalies in aerosol burdens span broad latitudinal ranges, particularly for sulfate burdens as the perturbations greatly exceed internal variability. In contrast, the radiative influence of aerosol burdens is in instances obscured by internal variability in both clear-sky and all-sky conditions, an effect remarked upon for COVID by Ming et al (2021), Gettelman et al (2020), andLoeb et al (2021). However, a statistically detectable negative anomaly in ensemble-mean net downward clear-sky shortwave flux (SW CS , Figure 2c) is coincident with anomalous AF BC burdens.…”
Section: Spatiotemporal Structure Of Covid and Af Climate Responsesmentioning
confidence: 94%
“…Some studies have also demonstrated decreased aerosol radiative forcing values (–24.3 W m −2 at surface and –16 W m −2 at TOA in the short wave) due to lower AODs during the lockdown period in Madrid ( Barragan et al, 2020 ) and considerable decreases in carbonaceous aerosol (BC and Brown Carbon) absorption in Wuhan ( Wang et al, 2021 ) and Athens ( Kaskaoutis et al, 2021 ). In addition, a decrease in the radiative forcing in East Asia was attributed to reductions in AOD, with one‐third of the reduced anomalies to be attributed to the lockdown, while the remaining was attributed to natural factors, such as meteorological variability and surface heterogeneity ( Ming et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This may be partly due to regional decreases in aerosol primary and precursor emissions caused by the response to the COVID-19 pandemic. Such decreases have, for example, reduced aerosol radiative effects off the coast of China, at least in cloud-free conditions (Ming et al 2020), which would weaken RFari. The data suggest a weakening trend in aerosol radiative forcing starting around 2015, but the trend would need to be sustained over a longer period to become statistically significant.…”
Section: E Atmospheric Circulation 1) Mean Sea Level Pressure and Related Modes Of Variability-r Allan And B Nollmentioning
confidence: 99%